2018
DOI: 10.3390/fluids3030054
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Droplets Using Cusp Formation behind a Drop Rising in a Non-Newtonian Fluid

Abstract: Abstract:The rising of a Newtonian oil drop in a non-Newtonian viscous solution is studied experimentally. In this case, the shape of the ascending drop is strongly affected by the viscoelastic and shear-thinning properties of the surrounding liquid. We found that the so-called velocity discontinuity phenomena is observed for drops larger than a certain critical size. Beyond the critical velocity, the formation of a long tail is observed, from which small droplets are continuously emitted. We determined that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Several past studies have shown that rising bubbles and droplets exhibit shape deformation due to the viscoelasticity of the ambient medium. 68,69 Therefore, to quantify the strength of elasticity of the ambient media in our experiments, we determined the Deborah number De (= Uτ / a ), defined as the product of polymer relaxation time ( τ ) and the characteristic strain rate . Here U is the droplet speed and a is the droplet diameter.…”
Section: Resultsmentioning
confidence: 99%
“…Several past studies have shown that rising bubbles and droplets exhibit shape deformation due to the viscoelasticity of the ambient medium. 68,69 Therefore, to quantify the strength of elasticity of the ambient media in our experiments, we determined the Deborah number De (= Uτ / a ), defined as the product of polymer relaxation time ( τ ) and the characteristic strain rate . Here U is the droplet speed and a is the droplet diameter.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies underscore a substantial influence of such normal stresses on flow fields containing suspended particles. In fact, the observed stress gradients possess the potential to significantly influence the trajectory of suspended particles or induce deformations in the shape of pliable particles navigating through such flow-fields [35][36][37][38][39]. While the Carreua-Yasuda model can reasonably predict the velocity profile and total shear stresses in steady shear flows, it completely neglects the generation of normal stresses.…”
Section: Flow-field In the Microchannel Conveying Single-phase Mc-pbs...mentioning
confidence: 99%
“…It is not clear about the reason for the appearance of negative wake, which is related to the non-Newtonian characteristics of the droplet such as the appearance of a pointed tail and the discontinuity of the rise velocity [56]. Capobianchi et al [56] argued that the concentration of viscoelastic stresses at the rear of the droplet is the main reason for the appearance and development of the sharp tail in the presence of high fluid viscoelasticity, while Poryles [58] experimentally demonstrated that the strong non-Newtonian behavior of the fluid is the main factor determining the length and width of the tail. When a Newtonian droplet moves upward in a non-Newtonian fluid with viscoelastic and shear-thinning properties, the shape of the droplet is closely linked to its volume and the non-Newtonian properties of the continuous-phase fluid.…”
Section: Viscoelastic Non-newtonian Fluidsmentioning
confidence: 99%